A Combination of Zinc and Pyridoxine Supplementation to the Diet of Laying Hens Improves Performance and Egg Quality - Kucuk, O.; Kahraman, A.; Kurt, I.; Yildiz, N.; Onmaz, A. C. (Springernature, 2008)
The objective of this study was to investigate whether zinc, along with pyridoxine, is effective in improving performance and egg quality of laying hens. One hundred and twenty, 28-week-old Hy-Line laying hens were assigned to four treatment groups, 30 hens each. The birds were fed a basal diet or the basal diet supplemented with either 30 mg of zinc/kg of diet, 8 mg of pyridoxine/kg of diet, or 30 mg of zinc plus 8 mg of pyridoxine/kg of diet. Feed conversion (P < 0.01) and egg production (P < 0.01) improved most when both zinc and pyridoxine were supplemented to the diet. Eggshell weights were also greatest (P < 0.01) when the diet was supplemented with both pyridoxine and zinc. Egg-shape index was, however, greatest with zinc-supplemented diet (P < 0.004). Haugh unit was greatest in eggs of hens fed a diet supplemented with both zinc and pyridoxine (P < 0.01). Dietary zinc and pyridoxine supplementations together increased plasma calcium and phosphorous concentrations (P < 0.002). The results of the present study suggested that zinc (30 ppm) and pyridoxine (8 ppm) supplements, when used together, are recommended in terms of a better performance and egg quality in laying hens.
Keywords: Zinc; Pyridoxine; Laying hens; Egg quality